Atezolizumab as first-line treatment in cisplatin-ineligible patients with locally advanced and metastatic urothelial carcinoma: a single-arm, multicentre, phase 2 trial. Issue 10064 (7th January 2017) - Balar, Arjun V; Galsky, Matthew D; Rosenberg, Jonathan E; Powles, Thomas; Petrylak, Daniel P; Bellmunt, Joaquim; Loriot, Yohann; Necchi, Andrea; Hoffman-Censits, Jean; Perez-Gracia, Jose Luis; Dawson, Nancy A; van der Heijden, Michiel S; et al.
Summary: Background: First-line chemotherapy for patients with cisplatin-ineligible locally advanced or metastatic urothelial carcinoma is associated with short response duration, poor survival, and high toxicity. This study assessed atezolizumab (anti-programmed death-ligand 1 [PD-L1]) as treatment for metastatic urothelial cancer in cisplatin-ineligible patients. Methods: For this single-arm, multicentre, phase 2 study, in 47 academic medical centres and community oncology practices in seven countries in North America and Europe, we recruited previously untreated patients with locally advanced or metastatic urothelial cancer who were cisplatin ineligible. Patients were given 1200 mg intravenous atezolizumab every 21 days until progression. The primary endpoint was independently confirmed objective response rate per Response Evaluation Criteria in Solid Tumors version 1.1 (central review), assessed in prespecified subgroups based on PD-L1 expression and in all patients. All participants who received one or more doses of atezolizumab were included in the primary and safety analyses. This study was registered withClinicalTrials.gov, numberNCT02108652 . Findings: Between June 9, 2014, and March 30, 2015, we enrolled 123 patients, of whom 119 received one or more doses of atezolizumab. At 17·2 months' median follow-up, the objective response rate was 23% (95% CI 16 to 31), the complete response rate was 9% (n=11), and 19 of 27 responses were ongoing. Median response duration was not reached. Responses occurred across all PD-L1 and poor prognostic factor subgroups. Median progression-free survival was 2·7 months (2·1 to 4·2). Median overall survival was 15·9 months (10·4 to not estimable). Tumour mutation load was associated with response. Treatment-related adverse events that occurred in 10% or more of patients were fatigue (36 [30%] patients), diarrhoea (14 [12%] patients), and pruritus (13 [11%] patients). One treatment-related death (sepsis) occurred. Nine (8%) patients had an adverse event leading to treatment discontinuation. Immune-mediated events occurred in 14 (12%) patients. Interpretation: Atezolizumab showed encouraging durable response rates, survival, and tolerability, supporting its therapeutic use in untreated metastatic urothelial cancer. Funding: F Hoffmann-La Roche, Genentech.